The "Iron Dog" in Northern Alaska - Hall, Jr., Edwin S. (Anthropologica, 2022)
The snowmobile, a recent technological innovation in northern Alaska, has caused dramatic changes in the lives of the Noatak Eskimos. Only a few quantitative measures of the nature and extent of cultural change attributable to the introduction of the snowmobile are now available, but some trends can be discerned.